Potemkin’s Brilliants: A Note on Russia’s Role in the Early Modern Diamond Trade - George E. Munro (Вивліоѳика)
Prince Grigorii Aleksandrovich Potemkin’s love of diamonds is well established. This article discusses several episodes in his life involving those gems, exploring their sources from discovery in the earth (India and Brazil) to their coming into the prince’s possession, and also references two other cases of consequential diamond loving in eighteenth-century Europe. Diamonds could represent much more than simply expensive embellishments